Nephroprotective effect of pigmented violacein isolated from Chromobacterium violaceum in wistar rats - Pang, Lei (Saudi J Biol Sci, 2020)
The present study aimed to analyze the nephroprotective property of violacein obtained from the bacterium, Chromobacterium violaceum. The nephrotoxicity in the animal model was induced by gentamicin, potassium dichromate, mercuric chloride, and cadmium chloride-induced nephrotoxicity in the Wistar rats was analyzed by measuring the serum creatinine, uric acid, and urea level. The present investigation revealed the nephroprotective property on convoluted proximal tubule (S1 and S2 segments) and the straight proximal tubule (S3 segment). Also, violacein significantly improved the renal function by the renal protective property on S2 segment of proximal tubule from the nephrotoxicity stimulated by mercuric chloride, potassium dichromate, cadmium chloride and gentamicin in animal models. Animal model studies revealed that violacein at 20 and 40 mg/kg p.o improved the renal function and significantly reduced the increased amount of uric acid, creatinine, and blood urea compared to the control.